Synthesis, characterization and electrochemistry of [Pd(PP)MeCl] compounds with 1, 1′-bis(phosphino)ferrocene ligands. (1st May 2021) - Hendricks, Michelle E.; Xu, Xiaoyu; Boller, Thomas R.; Samples, Evan M.; Johnson, Adam R.; Nataro, Chip
Graphical abstract: Compounds containing 1, 1ʹ-bis(phosphino)ferrocene ligands with the general formula [Pd(PP)MeCl] (PP = dcpf, dppdtbpf or dfurpf) were prepared and characterized. The oxidative electrochemistry of the compounds and their suitability as catalysts for the polymerizaton of phenylacetylene were studied. Abstract: Three new [Pd(κ 2 -PP)MeCl] (PP = 1, 1′-bis(dicyclohexylphosphino)ferrocene (dcpf), 1-diphenylphosphino-1′-ditert-butylphosphinoferrocene (dppdtbpf) or 1, 1ʹ-bis(5-methyl-2-furanylphosphino)ferrocene (dfurpf)) compounds were prepared and characterized. The X-ray crystal structure of [Pd(dppdtbpf)MeCl] was obtained which allowed for unambiguous determination of the cis / trans - relationship between the methyl and chloride ligands with respect to the different phosphine groups. The oxidative electrochemistry of the three new compounds as well as that of the reported [Pd(κ 2- PP)MeCl] (PP = 1, 1′-bis(diphenylphosphino)ferrocene (dppf), or 1, 1′-bis(diiso-propylphosphino)ferrocene (dippf)) and [Pd(κ 3 -dtbpf)Me]Cl (dtbpf = 1, 1′- bis(ditert-butylphosphino)ferrocene) was examined. The compounds with the κ 2 -bis(phosphino)ferrocene ligands react with sodium tetrakis(3, 5-bis(trifluoromethyl)phenylborate) to lose a chloride ligand and the catalytic activity of these compounds was investigated for the polymerization of phenylacetylene.